Окремі аспекти адміністративно-правового статусу суб'єктів виборчого процесу - Кальник, В. В.; Кальник, В. В.; Kal'nik, V. (Одеса : Юрид. л-ра, 2014)
Description of administrative-legal status of subjects of electoral process is given in the article, the legislation of Ukraine that regulates administrative-legal defense of participants of elections is analyzed, determination of administrative-legal status of electors is grounded.
Кальник В. В. Окремі аспекти адміністративно-правового статусу суб'єктів виборчого процесу / В. В. Кальник // Актуальні проблеми держави і права: зб. наук.пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.]; МОН України, НУ ОЮА. – Одеса: Юрид. л-ра, 2014. – Вип. 71. - С.32-37.
Keywords: Конституція України; Президент України; народний депутат України; виборчий процес; адміністративно-правовий захист; Конституция Украины; Президент Украины; народный депутат Украины; избирательный процесс; административно-правовая защита; The Constitution of Ukraine; President of Ukraine; deputy of peoples of Ukraine; electoral process; administrative and legal defense